Clinico-epidemiological profile of patients at children’s psychosocial care centers in São Bernardo do Campo: a cross-sectional study - Messias, Maialu Pedreira; Silva, Etienne de Miranda e; Andrade, Mariele Hertha de; Cavallo, Isabela Cristina Casanova; Galvão, Lucas Pequeno; Périco, Cintia de Azevedo Marques; Torales, Julio; Ventriglio, Antonio; Castaldelli-Maia, João Mauricio; Martins-da-Silva, Anderson Sousa (São Paulo Medical Journal, 2022)
BACKGROUND: Child and Adolescent Psychosocial Care Centers (Centros de Atenção Psicossocial, CAPSI) are dedicated centers for persistent psychiatric disorders, which provide an individualized therapeutic approach based on extra-hospital services. OBJECTIVES: We aimed to describe the clinico-epidemiological profiles of the patients seeking interventions at the CAPSIs. DESIGN AND SETTING: A cross-sectional study was conducted in two CAPSI in São Bernardo do Campo, SP, Brazil. One CAPSI is dedicated to the treatment of alcohol- and drug-related disorders, and the other to the treatment of other mental disorders. METHODS: In July 2017, we reviewed all active medical records of these two CAPSI, and ollected the patients information including sex, race, education, type of referral, initial complaints, psychiatric diagnoses, and medication utilization. RESULTS: Of the 233 patients, 69.5% were male and 42.5% lived with their immediate family. Most of the patients were referred from other health services. Complaints on admission included agitation and aggressive behavior (30.9%). Autism spectrum disorder (ASD) was the most prevalent diagnosis (46.8%), followed by depressive disorder (13.8%). Of the patients, 81.5% were on regular medical follow-up and 70.3% were on a single medication only. CONCLUSION: Aggression complaints are the most prevalent in CAPSI, and diagnoses of ASD and psychotic disorders are more common. This situation differs from most CAPSI that present school complaints as the most prevalent, in which diagnoses of attention-deficit/hyperactivity disorder and conduct disorders are likely to be more frequent. The epidemiological profile of each CAPSI should guide the implementation of human and structural resources targeting the most prevalent complaints and diagnoses.